A general two-phase debris flow model - Pudasaini, Shiva P. (Journal of Geophysical Research: Earth Surface, 2012)
This paper presents a new, generalized two‐phase debris flow model that includes many essential physical phenomena. The model employs the Mohr‐Coulomb plasticity for the solid stress, and the fluid stress is modeled as a solid‐volume‐fraction‐gradient‐enhanced non‐Newtonian viscous stress. The generalized interfacial momentum transfer includes viscous drag, buoyancy, and virtual mass. A new, generalized drag force is proposed that covers both solid‐like and fluid‐like contributions, and can be applied to drag ranging from linear to quadratic. Strong coupling between the solid‐ and the fluid‐momentum transfer leads to simultaneous deformation, mixing, and separation of the phases. Inclusion of the non‐Newtonian viscous stresses is important in several aspects. The evolution, advection, and diffusion of the solid‐volume fraction plays an important role. The model, which includes three innovative, fundamentally new, and dominant physical aspects (enhanced viscous stress, virtual mass, generalized drag) constitutes the most generalized two‐phase flow model to date, and can reproduce results from most previous simple models that consider single‐ and two‐phase avalanches and debris flows as special cases. Numerical results indicate that the model can adequately describe the complex dynamics of subaerial two‐phase debris flows, particle‐laden and dispersive flows, sediment transport, and submarine debris flows and associated phenomena. Key Points This paper presents a new, generalized and unified two‐phase debris flow model Includes non‐Newtonian viscous stress, virtual mass, generalized drag, buoyancy New model adequately describes complex two‐phase debris flow, sediment transport